"God, I Don't Want that Woman to Be Right about Me": Memorable Messages, Reflected Appraisals, and Women's Desistance. Issue 6 (18th August 2019) - Stone, Rebecca
ABSTRACT: Theories of desistance as a process of identity change are increasingly popular, with recent attention shifting to valued relationships, reflected appraisals, and emotion. The current study explores a control theory perspective on "memorable messages." Messages recalled by a sample of mothers involved in substance use and criminal offending demonstrate how these messages inform identity standards and guide behavioral decision-making. Women reveal the emotions and subsequent behavior related to satisfying or violating their identity standards as "good mothers." The study concludes with a discussion of the potential theoretical contributions of this framework, as well as the implications for future identity and desistance research.